Is overseas volunteering beneficial to the NHS? The analysis of volunteers' responses to a feedback questionnaire following experiences in low-income and middle-income countries. Issue 10 (16th October 2017) - Yeomans, Daniel; Le, Grace; Pandit, Hemant; Lavy, Chris
Abstract : Introduction: Locally requested and planned overseas volunteering in low-income and middle-income countries by National Health Service (NHS) staff can have benefits for the host or receiving nation, but its impact on the professional development of NHS staff is not proven. The Knowledge and Skills Framework (KSF) and Leadership Framework (LF) are two tools used by employers as a measure of individuals' development. We have used dimensions from both tools as a method of evaluating the benefit to NHS doctors who volunteer overseas. Methods: 88 NHS volunteers participating with local colleagues in Primary Trauma Care and orthopaedic surgical training courses in sub-Saharan Africa were asked to complete an online self-assessment questionnaire 6 months following their return to the UK. The survey consisted of questions based on qualities outlined in both the KSF and LF. Results: 85 completed responses to the questionnaire were received. In every KSF domain assessed, the majority of volunteers agreed that their overseas volunteering experience improved their practice within the NHS. Self-assessed pre-course and post-course scores evaluating the LF also saw a universal increase, notably in the 'working with others' domain. Discussion: There is a growing body of literature outlining the positive impact of overseas volunteering on NHS staff. Despite increasing evidence that such experiences can develop volunteers' essential skills, individuals often find it difficult to gain support of their employers. Our study, in line with the current literature, shows that overseas volunteering by NHS staff can provide an opportunity to enhance professional and personal development. Skills gained from volunteering within international links match many of the qualities outlined in both KSF and LF, directly contributing to volunteers' continued professional development.